RESIDU PESTISIDA GOLONGAN ORGANOFOSFAT KOMODITAS BUAH CABAI MERAH (Capsicum annuum L.) PADA BERBAGAI LAMA PENYIMPANAN - Surya Utami Dewi, I G A; Mahardika, I Gede; Antara, Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
PESTICIDES RESIDUAL OF ORGANOFOSPHATE CLASS OF RED CHILE (Capsicum annuum L.) ON VARIOUS STORAGE DURATION In order to control pests and diseases in red chili plants, farmers use pesticides was over as impact leaving residue in the chili. The purpose of this study was to determine type, dose and frequency of pesticides used by the farmers, as well as to determine the organophospate residual in chili on different storage times. This study was conducted in two phases namely survey to 10 respondent farmers in Baturiti district, Tabanan regency used questioner and treatment pilot study used different storage time from  0, 1 and 3 days samples took from Apuan Village, Baturiti, Tabanan. Class of organophosphate pesticide residue analysis conducted in Denpasar Branch Police Forensic Laboratory. The results showed dominant pesticides used was organophosphates profenofos (curacron) 60 % and klorpirifos (kaliandra) 20 %. Dose pesticides used was > 40 ml (> 4 bottle cover volume 10 ml) and > 40 gram (> 4 spoon) for tank volume 17 liter and also > 30 ml (> 3 bottle cover volume 10 ml) and > 30 gram (> 3 spoon) for tank volume 14 liter. Frequency of pesticides used by farmers on 1 plant season was 90 % more than 12 times and the other 10 % used frequency 10-12 times. Farmers do not comply dose and frequency with the pesticides used regulations. Analysis result showed that the treatment effect of different storage time is not real to organophosphate pesticide residues groupon red pepper. The average residues detected are indicating a trend with residue storage profenofos on day 0, 1 and day 3 for 1,20 mg/kg, 2,70 mg/kg and 1,37 mg/kg and the amount of chlorpyrifos residues on the storage day 0, day 1 and day 3 is 0,0027 mg/kg, 0,0039 mg/kg and 0,0021 mg/kg. Profenofos and chlorpyrifos residue content is still below the Maximum Residue Limit (MRL) under the provisions of MRL profenofos on red pepper, which is 5 mg/kg and chlorpyrifos, which is 0,5 mg/kg.